Biomechanics of single leg squat in physically active females: influence of dynamic knee valgus and exercise intervention - Sahabuddin, Farhah Nadhirah Aiman (2022)
Dynamic knee valgus (DKV) is generally associated with non-contact lowerlimb injuries, particularly in females. Thus, Study 1 compares the lower limb joints kinematic among physically active females with and without excessive DKV during single leg squats (SLS) at 45° and 60° knee flexion. Thirty four females were enlisted and categorized into two groups (i.e., normal and excessive DKV) based on the results of the drop vertical jump screening test. A DKV evaluation is based on the average knee FPPA range which is 7° to 13° for females in normal DKV group, while those in excessive DKV group have more than 13° of knee FPPA range. The 3-Dimensional (3D) SLS test (45° and 60° knee flexion) executed by the participants were captured with a Qualisys Track Manager System and analysed the kinematic data using an independent T-test. During 45° knee flexion, the dominant leg of normal DKV group showed a higher hip adduction angle (4.49±3.25°, t(32) = 2.371, p= 0.024) than the excessive DKV group (1.426±4.23°). Moreover, the normal DKV group displayed knee adduction (1.72±6.14°, t(32) = 2.291, p= 0.029), but the excessive DKV group demonstrated knee abduction (-3.620±7.40°) during SLS with dominant leg. During 60° knee flexion, the normal DKV performed with adducted dominant knee (0.223±0.07°, t(16.048) = 10.707, p=0.000) but abducted in the excessive DKV group (-4.478±1.81°). During 60° knee flexion with the non-dominant leg, the normal DKV group demonstrate SLS test with abducted knee (-1.127±0.89°, t(21.410) =-6.863, p= 0.000) while adducted in the excessive DKV group (0.635±0.57°). Furthermore, the non-dominant hip angle was abducted in the normal DKV group (0.635±0.54°, t(21.567) = 6.225, p= 0.000) but adducted (-0.245±0.23°) in the excessive DKV group during SLS. Therefore, females with excessive DKV had considerably different lower limb kinematics and movement control techniques than females with a normal DKV range. The findings emphasized the significance of DKV screening among physically active females, including the rationale for endorsing personalized exercise interventions to avoid lower limb non-contact injuries. Thus, the aim of Study 2 was to examine the effect of four weeks hip- and ankle-focused exercises on lower limb mechanics during SLS among physically active females. Thirty-six physically active females with excessive DKV, i.e., greater than 13° knee frontal plane projection angle (FPPA), were assigned equally to three groups: HIP, ANKLE, or control. Throughout 12 sessions across four weeks, the intervention groups underwent exercises focusing on either the hip (HIP group) or ankle (ANKLE group) musculatures. A training plan was not given to the control group. Next, all three groups demonstrated a similar SLS test protocol from study 1 (i.e., 45º and 60° of squat depths) were capture before and after intervention. A two-way ANOVA test was used to assess the data. During 45° SLS, there were interaction effects in the dominant knee (F (2.66) = 9.437, P = 0.001) and ankle (F (2.66) = 16.465, P = 0.001) sagittal moment between groups throughout four-weeks intervention. Meanwhile, the interaction effects in the hip extension angle for the dominant (F(2.66) = 12.032, P = 0.001) and non-dominant leg (F(2.66) = 3.618, P = 0.032) between groups were identified during 60° SLS after intervention. A fourweek intervention of hip-focused exercises affected lower limb biomechanics during SLS, especially in the sagittal plane. Thus, strengthening hip muscles, particularly the hamstring and quadriceps, through exercise may help to minimise excessive DKV in physically active females.